Varicoceles in Men With Non-obstructive Azoospermia: The Dilemma to Operate or Not - Kaltsas, Aris; Markou, Eleftheria; Zachariou, Athanasios; Dimitriadis, Fotios; Mamoulakis, Charalampos; Andreadakis, Sotirios; Giannakis, Ioannis; Tsounapi, Panagiota; Takenaka, Atsushi; Sofikitis, Nikolaos (Frontiers in Reproductive Health, 2022)
The literature on male reproductive medicine is constantly expanding, especially in diagnosing and treating infertility due to non-obstructive azoospermia. The percentage of azoospermic men in the general male population is about 1%, while it rises to 10-15% within a group of infertile men. Overall, men with non-obstructive azoospermia represent the majority (approximately 60 to 70%) of the total number of azoospermic individuals. Non-obstructed azoospermic men with varicocele represent a percentage equal to 4-14% of the population of non-obstructed azoospermic men. According to the findings of numerous studies on non-obstructive azoospermia, varicocele repair may contribute to the reappearance of spermatozoa in semen. However, the occurrence of spontaneous pregnancies is demonstrated in only a small percentage of cases. Additionally, it has been reported that the repair of varicocele increases the sperm recovery rate before the performance of sperm retrieval techniques. In addition, it increases the pregnancy rate in intracytoplasmic sperm injection (ICSI) program in men with non-obstructive azoospermia who have not demonstrated spermatozoa in the semen post-varicocelectomy. In addition, to infertility, varicocelectomy may increase the secretory function of Leydig cells, which subsequently results in improved androgen production and thus negating the need for testosterone replacement therapy. On the other hand, the benefit of varicocelectomy in patients with non-obstructive azoospermia is still debatable. The current review study aims to provide a critical and extensive review of varicocele repair in males with non-obstructive azoospermia. Focusing on the impact of varicocele repair on sperm retrieval rates and the influence on the ICSI outcomes for those couples who remain negative for spermatozoa post-varicocelectomy.